1998
DOI: 10.1177/0013916598301002
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Inner-City Landscapes

Abstract: How would inner-city residents respond to the incorporation of trees and grass in their neighborhoods? Law enforcement officials have argued that, in these settings, trees and other forms of vegetation increase fear. Tree density, tree placement, and levels of grass maintenance were manipulated in photo simulations of neighborhood outdoor space. One hundred residents of Chicago's Robert Taylor Homes living adjacent to the space rated the images with respect to preference and sense of safety. Although tree plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(101 citation statements)
references
References 20 publications
6
75
1
2
Order By: Relevance
“…Despite some claims that green spaces can be perceived as dangerous (Herzog andFlynn-Smith 2001, Van Winsum-Westra andBoer 2004), Maas and colleagues (2009) concluded that green space in people's living environment is generally associated with enhanced feelings of social safety and that this relationship is concurrent with the positive relationship between green space and people's health that has been found in the literature. Kuo et al (1998) and Kuo and Sullivan (2001) present research demonstrating that exposure to trees in urban settings can foster a sense of safety and reduce crime rates, thus contributing to social well-being. Therefore, considering the voluminous research reviewed above, the 'seeing green' implications for human health and well-being of so-called 'plant-people interactions' (Salick 1995, Elings 2006, Relf 2006 appear to be well documented.…”
Section: Restorative Environmentsmentioning
confidence: 97%
“…Despite some claims that green spaces can be perceived as dangerous (Herzog andFlynn-Smith 2001, Van Winsum-Westra andBoer 2004), Maas and colleagues (2009) concluded that green space in people's living environment is generally associated with enhanced feelings of social safety and that this relationship is concurrent with the positive relationship between green space and people's health that has been found in the literature. Kuo et al (1998) and Kuo and Sullivan (2001) present research demonstrating that exposure to trees in urban settings can foster a sense of safety and reduce crime rates, thus contributing to social well-being. Therefore, considering the voluminous research reviewed above, the 'seeing green' implications for human health and well-being of so-called 'plant-people interactions' (Salick 1995, Elings 2006, Relf 2006 appear to be well documented.…”
Section: Restorative Environmentsmentioning
confidence: 97%
“…It seems that the effect of tree density on safety depends on context. Kuo et al (1998) found that tree density and grass maintenance increased both preference and a sense of safety for a sample of low-income residents in Chicago, Illinois, USA. Assessing the effects of tree cover on crime in Portland, Oregon, USA, Donovan and Prestemon (2012) found that trees, as an attribute of a well-kept neighborhood, might give criminals the impression of being observed by authority, thus deterring crime occurrence.…”
Section: Proximity To Public Green Areas and Neighborhood Parksmentioning
confidence: 95%
“…Urban parks fulfill important immaterial and non-consumptive human needs [4]. It reduces stress [5] and results in a good mental health [6] [7] provide sense of peacefulness & tranquility [8] and reduce aggression [9]. Hospitalized patients who are able to view trees from their windows recover more quickly than those who see only buildings [10].…”
Section: Introductionmentioning
confidence: 99%
“…Parks increase social integration and interaction among neighbors [12] and promote social ties [9]. They provide get-together spot for kinfolk and social groups, as well as for individuals of various ages and economic status.…”
Section: Introductionmentioning
confidence: 99%